Драматична поема Лесі Українки: психологічні фактори творення жанру - Левчук, Юлія; Levchuk, Yuliia (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Наукове дослідження зосереджено на проблемі жанру драматичної поеми у творчості Лесі Українки як центрального явища. Використано методику когнітивного підходу до аналізу жанрів, а саме концепцію Ж. М. Шеффера щодо жанру як інструменту для втілення творчих задумів автора, а не статичного вмістилища твору. Scientific research has focused on the problem of the genre of the dramatic poem as a central phenomenon in the work of Lesia Ukrainka. A significant part of the article is devoted to the psychological nature of the genre the dramatic poem, in particular, were the parallels between the epic and the lyrical and the types of characters of Lesia Ukrainka’s parents. It turned out that this division of people it is possible, as in the most general meaning of epic and lyric poetry is as characters extrovert/introvert. Special attention is paid to the author’s dramatic poem “Rufin and Priscilla” (1906−1908), as this work is characterized by epic, scale. Besides the play “Autumn Tale” (1905) was analyzed for the presence of fantastic elements and genre parody of the knight novel. It turned out that the dramatic poem of Lesia Ukrainka is a complex structured genre, based on the conflict of lyrical and epic, and supplemented by the author’s own lyricism inherited from the writer’s father.
The Dramatic Poem of Lesia Ukrainka: the Psychological Factors of the Genre Creating.
Keywords: Леся Українка; драматична поема; драма; епічність; ліричність; жанр; Lesia Ukrainka; the dramatic poem; drama; epic; lyricism; genre